2017
DOI: 10.1136/bmjopen-2016-015410
|View full text |Cite
|
Sign up to set email alerts
|

Low alcohol consumption and pregnancy and childhood outcomes: time to change guidelines indicating apparently ‘safe’ levels of alcohol during pregnancy? A systematic review and meta-analyses

Abstract: ObjectivesTo determine the effects of low-to-moderate levels of maternal alcohol consumption in pregnancy on pregnancy and longer-term offspring outcomes.Search strategyMedline, Embase, Web of Science and Psychinfo from inception to 11 July 2016.Selection criteriaProspective observational studies, negative control and quasiexperimental studies of pregnant women estimating effects of light drinking in pregnancy (≤32 g/week) versus abstaining. Pregnancy outcomes such as birth weight and features of fetal alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
125
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(137 citation statements)
references
References 52 publications
5
125
2
Order By: Relevance
“…Many studies have shown that alcohol consumption during pregnancy has increased worldwide. [17][18][19] Notably, alcohol consumption during pregnancy has been found to cause CHD in foetuses. 20,21 However, the mechanistic link between alcohol and CHD is still largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that alcohol consumption during pregnancy has increased worldwide. [17][18][19] Notably, alcohol consumption during pregnancy has been found to cause CHD in foetuses. 20,21 However, the mechanistic link between alcohol and CHD is still largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that heavy alcohol use in pregnancy can cause foetal alcohol syndrome (Mukherjee, Hollins, & Turk, 2006), resulting in physical and cognitive impairments (Coles, Platzman, Lynch, & Freides, 2002;Gibbard, Wass, & Clarke, 2003;Guerri, Bazinet, & Riley, 2009). However, even at levels of alcohol consumption below that required for foetal alcohol syndrome, exposure to alcohol during gestation has been shown to be associated with detrimental outcomes in the offspring, such as being small for gestational age (Mamluk et al, 2017), and birth complications such as pre-eclampsia and placental abruption (Salihu et al, 2011), as well as behavioural outcomes such as increased risk of externalising disorders (Sayal et al, 2014) and internalising disorders (Sood et al, 2001;Walthall, O'Connor, & Paley, 2008). However, much research in this area has been conducted on Intrauterine alcohol and depression 4 offspring at an early age, with less research in older age groups to establish whether these associations persist into adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals exposed to low to moderate levels of alcohol do not typically present with facial, anthropometric or cognitive abnormalities. Indeed, a large systematic review found weak evidence of adverse effects from low to moderate alcohol exposure 7 However, previous research has suggested that low to moderate alcohol exposure may have modest adverse effects on offspring cognition and school performance 8; 9 and sub-clinical facial differences have been observed between low to moderately exposed, and unexposed individuals 10 . Variation (within the normal range) in facial morphology may be a marker of alcohol-related cognitive impairments; children exposed to alcohol with more FAS like facial symptoms have been shown to perform worse on psychometric tests 11 .…”
Section: Introductionmentioning
confidence: 99%